Bridging the gap between real world polar science and the classroom - Robertson, William; Lougheed, Vanessa; Tweedie, Craig; Velasco, Aaron; Garcia, Claudia (ScholarWorks@UTEP, 2009)
The International Polar Year - Research and Educational Opportunities in Antarctica for Minorities (IPY-ROAM) program was designed to increase minority participation in polar science by immersing participants in an academic program that included a trip to Antarctica. The IPY-ROAM program was focused on increasing the public understanding of the Polar Regions and stimulating a new interest in polar science. This effort was coordinated by faculty from the University of Texas at El Paso (UTEP) and was implemented to positively contribute to the intense, internationally coordinated IPY scientific campaign. Through a grant from the National Science Foundation (NSF), a team of UTEP researchers developed a unique and life-changing opportunity for university students and high-school teachers to travel to Antarctica. The goal of the program was for participating students and teachers to learn more about the Polar Regions and to acquire first hand experience in field-based research and Antarctic system science.